Study the effect of fish in alternating electrical properties of copper oxide membranes CuO (Baghdad Science Journal, 2006)
In this research study the effect of fish in alternating electrical properties at room temperature copper oxide membranes and fish prepared in a manner different thermal spraying chemical on a thin glass bases and heated